Screening of Ketoprofen-Poloxamer and Ketoprofen-Eudragit solid dispersions for improved physicochemical characteristics and dissolution profile - Ravi Yashwant Savardekar; Amol Shantinath Sherikar (Universidade de São Paulo, 2020)
The aim of the present study was to enhance the dissolution rate of an NSAID drug Ketoprofen by formulating it into solid dispersions with water soluble carrier Poloxamer 188 and Eudragit S 100. The solid dispersions of Ketoprofen with Poloxamer 188 were prepared at 1:1, 1:1.5 and 1:2 (Ketoprofen: Poloxamer 188) ratio by Solvent evaporation methods. The same concentration ratio was used for the preparation of solid dispersion with Eudragit S 100 by melting/fusion technique. Further, solid dispersions were investigated by solubility, ATR-FTIR, XRD, DSC, surface morphology, in-vitro dissolution and accelerated stability study. Results demonstrated that both Poloxamer 188 and Eudragit S 100 improve solubility of drugs by 8-10 folds. The result of ATR-FTIR study showed the slight shifting/broadening of principle peaks. In vitro dissolution studies showed that in the solid dispersion system containing Ketoprofen: Poloxamer 188 batch P2 (1:1.5) gives faster dissolution rate of Ketoprofen than the physical mixtures. The solid dispersion with Eudragit S 100, batch E1 (1:1) gives faster dissolution rate of Ketoprofen than the physical mixtures. In phase solubility study with Poloxamer 188 showed concentration dependent solubilization of drug but Eudragit S 100 produced opposite result. The effect of pH on solubility of Eudragit S 100 was carried out which showed solubility at pH 7.4. The dissolution profile of solid dispersion with Eudragit S 100 at pH 7.4 gives excellent result. The Accelerated stability of solid dispersions & its physical mixtures were studied at 400±2 °C/75 ± 5% RH for a period of 1 month. In these studies, Solid Dispersion batches produced an unstable formulation. The Ketoprofen solid dispersions with Poloxamer 188 and Eudragit S 100 could be introduced as a suitable form with improved solubility.